Colorimetric measurement of carbohydrates in biological wastewater treatment systems: A critical evaluation. (1st May 2016) - Le, Chencheng; Stuckey, David C.
Abstract: Four laboratory preparations and three commercially available assay kits were tested on the same carbohydrate samples with the addition of 14 different interfering solutes typically found in wastewater treatment plants. This work shows that a wide variety of solutes can interfere with these assays. In addition, a comparative study on the use of these assays with different carbohydrate samples was also carried out, and the metachromatic response was clearly influenced by variation in sample composition. The carbohydrate content in the supernatant of a submerged anaerobic membrane bioreactor (SAMBR) was also measured using these assays, and the amount in the different supernatant samples, with and without a standard addition of glucose to the samples, showed substantial differences. We concluded that the carbohydrates present in wastewater measured using these colorimetric methods could be seriously under- or over-estimated. A new analytical method needs to be developed in order to better understand the biological transformations occurring in anaerobic digestion that leads to the production of soluble microbial products (SMPs) and extracellular polymeric substance (EPS). Graphical abstract: Highlights: Colorimetric measurement of carbohydrate are considered simple to perform, but the accuracy of their results are poor. The use of glucose as a reference standard often results in misleading concentrations. These colorimetric assays have been shown to be susceptible to 14 common solutes found in wastewater. Due to wide deviation, these colorimetric methods are inappropriate for the investigation of wastewater samples.